Different prognosis between severe and very severe obstructive sleep apnea patients; Five year outcomes. Issue 6 (December 2020) - Hamaoka, Takuto; Murai, Hisayoshi; Takata, Shigeo; Hirai, Tadayuki; Sugimoto, Hiroyuki; Mukai, Yusuke; Okabe, Yoshitaka; Tokuhisa, Hideki; Takashima, Shin-Ichiro; Usui, Soichiro; Sakata, Kenji; Kawashiri, Masa-Aki; et al.
Highlights: Obstructive sleep apnea (OSA) is a well-known risk factor for cardiovascular diseases (CVD). Apnea hypopnea index (AHI) > 30 events/h is regarded as most severe OSA. In our previous report, very severe OSA (AHI > 55) had highest sympathetic nerve activity. In this study, very severe OSA showed higher rate of CVD events compared to severe OSA. More detailed stratification is needed for OSA to prevent CVD. Abstract: Background: Obstructive sleep apnea (OSA) is characterized by augmented sympathetic nerve activity. In our previous study, patients with OSA and an apnea-hyperpnea index (AHI) > 55 events/h showed increased single-unit muscle sympathetic nerve activity compared to patients with OSA and AHI of 30–55 events/h. However, the prognostic impact in these patients remains unclear. Methods: Ninety-one OSA patients were included. All patients who had indication for continuous positive airway pressure (CPAP) were treated with CPAP. Patients were divided into three groups: mild/moderate OSA (S), AHI < 30 events/h ( n = 44); severe OSA (SS), AHI 30–55 events/h ( n = 29); and very severe OSA (VSS), AHI > 55 events/h ( n = 18). The primary endpoint was a composite outcome composed of death, cardiovascular events, stroke, and heart failure with hospitalization. Results: In the 5-year follow-up, the primary event rate in the SS group [3 events (7%)] was the same as that in the S group [3 events (10%)]. However, the VSS group showed a significantly higher primary event rate among the three groups [6 events (33%), p < 0.05]. In Cox regression analysis, the VSS group had the highest hazard ratio compared to other risk factors. Conclusions: CPAP was effective for preventing cardiovascular disease in patients with severe OSA, however patients with very severe OSA still had a high event rate, indicating that CPAP treatment might be insufficient to reduce the OSA-related risk burden in patients with very severe OSA. Additional systemic medical treatment for CPAP might be needed in patients with very severe OSA.